Stable Luminescent Composite Microspheres Based on Porous Silica with Embedded CsPbBr3 Perovskite Nanocrystals. Issue 7 (12th May 2020) - Ushakova, Elena V.; Cherevkov, Sergei A.; Sokolova, Anastasiia V.; Li, Yanxiu; Azizov, Ruslan R.; Baranov, Mikhail A.; Kurdyukov, Dmitry A.; Yu Stovpiaga, Ekaterina; Golubev, Valery G.; Rogach, Andrey L.; Baranov, Alexander V.
Abstract: Lead halide perovskite nanocrystals are attracting a lot of attention due to their superior optical properties, such as narrow emission bandwidths, and high photoluminescence quantum yields. Still, they are far from practical implementation, since they can rather easily degrade under ambient conditions, and even more so at high humidity, temperature, and UV light exposure, which has triggered on‐going search for the suitable protective host matrices. We report a luminescent composite material based on porous silica microspheres (0.5 μm in diameter) with embedded CsPbBr3 perovskite nanocrystals. This composite shows increased stability in terms of preserving photoluminescence of the CsPbBr3 nanocrystals, while further encapsulation in polymer shells using sequential layer‐by‐layer assembly of the oppositely charged polyelectrolytes poly(allylamine hydrochloride) and poly(sodium 4‐styrenesulfonate) results in water dispersible luminescent microspheres. The availability of such samples may expand the use of light‐emitting perovskite nanocrystals in diverse biological applications, including imaging and sensing in highly scattering media. Abstract : Luminescent composite silica‐based microspheres impregnated with CsPbBr3 perovskite nanocrystals were fabricated, whose photoluminescence was preserved at ambient conditions for several months. Layer‐by‐layer deposition of polymers on top of these composite microspheres resulted in water‐dispersible luminescent samples.